(untitled) (Research, Society and Development, 2022)
The demand for rehabilitative treatments has been a constant search in dental offices, especially in the area of aesthetics, where the demand is the desire for a perfect smile, that is, harmonic, voluminous and white. The purpose of this article is to address the importance of individualized planning and discuss composite resins and restoration techniques that have been improved to promote quality of life for patients. Method: this work was carried out from bibliographic searches in Google Scholar and Pubmed databases using articles in Portuguese, which were published between the years 2011 and 2022. Discussion: this literature review talks about the restorative materials that were modified in relation to their characteristics, such as thickness of the elements, composition and optical properties, these transformations were made thinking about the best results that can be offered. As well as resins, techniques have also been improved, such as layering techniques, where they are composed of several layers of resin depending on the case. Conclusion: the planning and the correct techniques used offer quality of life for patients, therefore, knowledge about the morphology and the properties of composite resins are essential.